Jogos no processo de ensino-aprendizagem nas aulas de química geral em um curso de Ciência e Tecnologia - Silva, Maxwell da (Universidade Federal Rural do Semi-Árido, 2020)
An alternative that can be worked in the classroom to reduce this problem is to carry out recreational activities, among them is the use of games. The project entitled Games in the teaching-learning process in general chemistry classes in a science and technology course, aimed to evaluate how the practice of playful games during classes in the general chemistry curriculum component can influence the learning of a group of students of the Bachelor of Science and Technology course at the Federal Rural University of the Semi-arid - UFERSA at Campus Angicos / RN. The project was divided into stages, the first was a bibliographic search in books and magazines with grades A1 to B2, in the area of Chemistry Teaching, to identify and select a didactic game that works with concepts on the Periodic Table, the second the board and game pieces were made, the third game was performed and the LIkERT scale was applied and in the fourth and last stage the data were analyzed. Where 35 students participated in the game and were divided into 7 groups with 5 students in each group on two boards and at the end of the activity answered the statements. However, he found that the use of games is beneficial, improves performance and motivates students and that their use in chemistry classes helps in the teaching-learning process.
Artigo
Keywords: Ensino-aprendizagem; Atividade lúdica; Ensino de química; Tabela periódica; Teaching-learning; Playful activity; Chemistry teaching; Periodic table; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA